Identification and characterization of pancreatic infections in severe and critical acute pancreatitis patients using 16S rRNA gene next generation sequencing - Sun, Ning; Chen, Yong; Zhang, Jiaxun; Cao, Jin; Huang, Hongjuan; Wang, Jie; Guo, Wentao; Li, Xiaojun (Frontiers in Microbiology, 2023)
This study aimed to identify the bacterial composition in the pancreatic fluid of severe and critical acute pancreatitis (SAP and CAP) patients. A total of 78 pancreatic fluid samples were collected from 56 SAP and CAP patients and analysed by aerobic culture and 16S rRNA gene next-generation sequencing. The clinical data of the patients were obtained from the electronic medical records. Among the total 78 samples, 16S rRNA gene NGS identified a total of 660 bacterial taxa, belonging to 216 species in 123 genera. The predominant aerobic bacteria included Klebsiella pneumoniae, Acinetobacter baumannii, and Enterococcus faecium, while the predominant anaerobic bacteria included Bacteroides, Dialister invisus, and Olsenella uli. As compared to aerobic culturing, 95.96% (95/99) of the aerobic cultured bacteria were detected using the 16S rRNA gene NGS. The pancreatic infections in the SAP and CAP patients might originate not only from the gut but also from the oral cavity and airways as well as related environments. Dynamic analysis of bacterial profile and abundance showed that some bacteria with low abundance may become the main pathogenic bacteria. There were no significant differences in the bacterial diversity between SAP and CAP. This study also suggests that the 16S rRNA gene NGS is more suitable for the identification of polymicrobial infections.